Interactions of copper, selenium, and vitmain E for weanling swine - Thulin, A.J.; Pollmann, D.S.; Blecha, Frank; Kennedy, G.A.; Whetter, P.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One-hundred and sixty pigs were utilized to evaluate possible interactions between copper (Cu), selenium (Se), and vitamin E (E) on growth and immunity of starter pigs. Copper (260 ppm) added to the diet did not effect Se and/or E utilization for growth, feed efficiency (FE), or immunity. However, addition of 260 ppm of Cu to the diets of starter pigs resulted in an 8% improvement in feed intake (FI) and a 13% improvement in average daily gain (ADG) for the first 2 wk on test. There was no effect on performance due to E additions. However, addition of .3 ppm Se to the diets resulted in an overall 5% improvement in FE and a 7% improvement in ADG. Additions of dietary Cu, Se and E had no effect on immunity and no evidence of tissue lesions or symptoms typical of Se and E deficiency were found.
Keywords: Swine; Copper; Selenium; Vitamin E; Weanling